DAMPAK PENGEMBANGAN POS LINTAS BATAS NEGARA (PLBN) WINI PADA KAWASAN PERBATASAN RI-RDTL - Chrysogonus Koko Kause; Maria Indryani Hewe Tiwu; Novi Theresia Kiak (E-Jurnal Ekonomi Pembangunan, 2024)
ABSTRACT This research aims to describe the socio-economic activities that occur between Indonesia and Timor Leste, as well as formulating several border region development strategies. The approach used is descriptive qualitative, with Milles and Huberman and SWOT analysis. The development of PLBN Wini has had a positive impact on socio-economic life. The social impact felt is ease of access to public facilities and infrastructure. The economic aspect that occurs is that people find it easy to access the market, job opportunities are opened. Wini's border area development strategy, namely (1) Efforts to develop salt for consumption and processing of beef related to Featured Products in Border Markets and E-Market Places (2) Efforts for training and development of cattle farming and consumption salt to increase the income of border area communities (3 ) Processing salt in packages so that it can be marketed and can process cattle from meat, milk, internal organs, bones to skin which can be used for consumption or making crafts to support the tourism sector. This research is a recommendation for the regional government of North Central Timor Regency for the development of the Wini State Cross Border Post area, North Insana District. Keywords: Strategy, Regional Development, Borden Region